Comparative transcriptomic and metabolomic study reveal that exogenous 24‐epiandrosterone mitigate alkaline stress in broomcorn millet (Panicum miliaceum L.) via regulating photosynthesis and antioxidant capacity. Issue 4 (14th February 2023) - Ma, Qian; Wu, Enguo; Wang, Honglu; Feng, Yu; Zhao, Lin; Feng, Baili
Abstract: Globally, land alkalinization affecting agricultural development. Considering the increasingly serious effects of alkaline stress on agriculture and environment, phytoremediation may be an efficient way to addressed land alkalinization. Broomcorn millet ( Panicum miliaceum L.) is a saline‐alkaline‐tolerant crop and bioenergy crop. However, the molecular mechanism of alkaline response on broomcorn millet remains large gap. To explore the alkaline stress on broomcorn millet and the mitigation of 24‐epicastasterone (BR), the effects of CK (nutrient solution only), CB (nutrient solution + 0.5 mg L −1 BR), AS (alkaline stress), and AB (alkaline stress + 0.5 mg L −1 BR) on TA289 (alkaline‐tolerant) and SA223 (alkaline‐sensitive) were investigated. Alkaline stress enhanced reactive oxygen species and membrane lipid peroxidation. BR boosted antioxidant enzyme activities to reduce oxidative stress. Simultaneously, BR attenuated Na + toxicity and maintained ion homeostasis. Additionally, BR significantly maintained the physiological structure and photosynthetic properties. Transcriptomic and metabolomic analyses were applied to further evaluate the effect of BR on photosynthetic and antioxidant defense. The results showed that BR significantly reduced the transcriptional responses of photosynthesis and antioxidant defense and promoted the accumulation of effective metabolites such as biliverdin, l ‐glutamate, and phosphoric acid. Taken together, BR application can significantly alleviate the damage of alkaline stress to broomcorn millet by altering transcriptional expression and metabolite accumulation and is a simple and effective strategy to alleviate alkaline stress. This study reveals the molecular mechanism of BR to enhance photosynthetic capacity and antioxidant defense of broomcorn millet under alkaline stress, which provides theoretical support for the cultivation of bioenergy crops on alkaline lands and the breeding of alkaline‐tolerant bioenergy varieties. Abstract : Globally, land alkalinization affecting agricultural development. Phytoremediation is an efficient way to addressed land alkalinization. Broomcorn millet ( Panicum miliaceum L.) is a saline‐alkaline‐tolerant crop and bioenergy crop. In this study, the growth of broomcorn millet under CK (nutrient solution only), CB (nutrient solution + 0.5 mg L −1 BR), AS (alkaline stress) and AB (alkaline stress + 0.5 mg L −1 BR) were investigated. The results revealed the molecular mechanism of BR to alleviate alkali stress, which provided theoretical support for the cultivation of bioenergy crops on alkaline lands and the breeding of alkaline‐tolerant varieties.